Contemporary Management of Hepatic Trauma: What IRs Need to Know - Gilyard, Shenise; Shinn, Kaitlin; Nezami, Nariman; Findeiss, Laura K.; Dariushnia, Sean; Grant, April A.; Hawkins, C. Matthew; Peters, Gail L.; Majdalany, Bill S.; Newsome, Janice; Bercu, Zachary L.; Kokabi, Nima (Seminars in Interventional Radiology, 2020)
Trauma remains one of the leading causes of death in the United States in patients younger than 45 years. Blunt trauma is most commonly a result of high-speed motor vehicular collisions or high-level fall. The liver and spleen are the most commonly injured organs, with the liver being the most commonly injured organ in adults and the spleen being the most affected in pediatric blunt trauma. Liver injuries incur a high level of morbidity and mortality mostly secondary to hemorrhage. Over the past 20 years, angiographic intervention has become a mainstay of treatment of hepatic trauma. As there is an increasing need for the interventional radiologists to embolize active hemorrhage in the setting of blunt and penetrating hepatic trauma, this article aims to review the current level of evidence and contemporary management of hepatic trauma from the perspective of interventional radiologists. Embolization techniques and associated outcome and complications are also reviewed.
Keywords: liver trauma; injury; hepatic; embolization; interventional radiology